2010
DOI: 10.1007/s00445-010-0379-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyroclastic flow hazard assessment at Somma–Vesuvius based on the geological record

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 72 publications
(127 reference statements)
4
94
0
1
Order By: Relevance
“…Cavache and Williams 1992), these lithic-rich PDC deposits, have extents similar to those of pumice-rich PDC deposits (e.g. Gurioli et al 2010) and have a lethal temperature, as we found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Cavache and Williams 1992), these lithic-rich PDC deposits, have extents similar to those of pumice-rich PDC deposits (e.g. Gurioli et al 2010) and have a lethal temperature, as we found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Both tephra fallout and PDCs are likely to happen and they could supply fresh pyroclastic material onto the slopes of the volcanic edifice as well as on the Apenninic reliefs toward the northeast, east and southeast of Somma-Vesuvius (Cioni et al, 1999;Gurioli et al, 2010). In this situation, tephra may be remobilized by erosive runoff of the fine-grained upper-part of the deposit and/or by shallow gravitational failures as the coarser-grained underlying deposit is exposed (Zanchetta et al, 2004a;Sulpizio et al, 2006).…”
Section: Multihaz Applied To Somma-vesuviusmentioning
confidence: 99%
“…The natural variability of these eruptions, in terms of tephra-fallout dispersal and PDC inundation, is quite large (Cioni et al, 2008;Gurioli et al, 2010;Sandri et al, 2016;Tierz et al, 2016a). In this paper, we quantify this aleatory uncertainty in pyroclastic volume over different catchments around SommaVesuvius (Figure 5), by computing probabilistic hazard curves (e.g., Rougier et al, 2013) of this variable for tephra fallout and dense PDCs.…”
Section: Tephra-fallout and Pdc-deposit Volumesmentioning
confidence: 99%
“…In addition, volcanic eruptions are not the only cause of damage in volcanic areas. For example, lahars and mudflows may not only occur during volcanic unrest, but also may be triggered by heavy rains, months after the eruption, as at Pinatubo in 2001(Hayes et al, 2002 and more recently at Merapi volcano in 2010 (Lavigne et al, 2011;Bignami et al, 2013). On Mount Cameroon, landslides that are not related to contemporary volcanic activity are a major concern (Ayonghe et al, 2004).…”
Section: Hazardmentioning
confidence: 99%
“…This involves a structured collection of expert guesses together with the associated uncertainties. This approach may be applied for case studies such as at Vesuvius, where a large amount of information is available on past volcanic events thanks to historical reports since Roman times, and numerous sedimentology studies (Acocella et al, 2006a;Gurioli et al, 2010, and references therein). In less known volcanoes is an approach that could become more widespread with the sharing and dissemination of historical eruption data (Marzocchi et al, 2004;Sandri et al, 2012).…”
Section: Knowledge Collection At a Target Volcano And Event Tree Consmentioning
confidence: 99%